Upaya dan Manfaat Pelestarian Sungai Masyarakat Panyabungan Barat Sumatera Utara Berbasis Kearifan Lokal Lubuk Larangan - Nanda Eska Anugrah Nasution; Chairany Rizka; Imaniah Bazlina Wardani; Risma Nurlim (Institut Agama Islam Negeri Kerinci, 2024)
The conservation of rivers in West Panyabungan District, is of utmost importance due to their significance as a vital water source for daily activities and their significant impact on people's livelihoods. The objective of this study is to examine the endeavours and advantages of ecological preservation utilising the indigenous knowledge of the Lubuk Larangan River by the inhabitants of West Panyabungan, North Sumatra. This study employs a descriptive qualitative methodology. The data utilised consists of primary data collected by field research, specifically through field observations, in-depth interviews, and focus group discussions. Key informants refer to prominent individuals within the community, including traditional elders, village officials in the surrounding area, managers of Lubuk Larangan, and members of the surrounding community. The research employed data analysis approaches: data collecting, data condensation, data presentation, and the derivation and validation of conclusions. The technique used for data validity assessment is the triangulation of sources and techniques. The research findings indicate that environmental preservation in Lubuk Larangan is achieved through the continuation of traditional practices that have been passed down through generations, collaborative efforts to implement and safeguard these practices, and the implementation of local wisdom to protect the village environment.